Anal incontinence severity assessment tools used worldwide - Rusavy, Zdenek; Jansova, Magdalena; Kalis, Vladimir (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2014)
OBJECTIVE: To conduct an international survey of anal incontinence assessment tools and the need to evaluate frequency of occurrence of fecal urgency. METHODS: A questionnaire on the use of anal incontinence assessment tools was distributed between May and December 2012 among clinicians and researchers dealing with anal incontinence, primarily in North America, Europe, and Asia. RESULTS: A total of 143 responses were collected from 56 (39.2%) obstetricians, gynecologists, and urogynecologists; 71 (49.7%) colorectal surgeons, proctologists, and general surgeons; and 16 (11.2%) physiotherapists, theoretical scientists, and gastroenterologists. Fourteen different tools were reported-most commonly Wexner score (n=78; 48.8%) and St Mark's score (n=29; 18.1%). No scoring system was used by 24 (16.8%) respondents. Thirty-four (28.6%) used multiple tools. There was variation in the reasons given for scoring the frequency of fecal urgency as 4 points when using St Mark's score. Of 96 respondents responding to a query about modifying the St Mark's score, 88 (91.7%) agreed that fecal urgency should be scored according to the frequency of occurrence. CONCLUSION: Although the Wexner score neglects fecal urgency, it is the most commonly used scoring system. The study contributes to the standardization of terminology and reproducibility of results in research and clinical management of anal incontinence.
Keywords: Humans; Fecal incontinence; stupeň závažnosti nemoci; Fecal Incontinence; Anal incontinence; celosvětové zdraví; ženské pohlaví; Severity of Illness Index; Fecal urgency; Female; fekální inkontinence; Survey; Global Health; průzkumy a dotazníky; Surveys and Questionnaires; lidé